(untitled) (Revista Venezolana de Salud Pública, 2018)
Since the beginning of Cardiology in the world and then started as specialty in Venezuela history have occurred various events that influenced the development of the Cardiovascular Program in Venezuela created to become a national response to cardiovascular disease as a public health problem. In this context, this historical note particular places emphasis on the commencement of the Cardiovascular Program in Lara State, taking into account the set of individual and institutional situations that gave the necessary momentum, before 1976, for its establishment. In accordance with the foregoing, this factual account is intended to understand the evolution of the program in the region, which, following the same doctrinal basis of the national proposal and implementing different strategies, has achieved its permanence in time. By the way of closure, in the historical note, the strengths of the Cardiovascular Program in the state of Lara, Which through time have allowed it to consolidate itself as a unique and successful experience in the country, namely, the organized participation of the community, the link with the doctrinal issues, the organization and articulation of services by levels of resolution capacity, The teaching-assistance linkage, complementary sources of program financing and teamwork.